The Effect of Social Support and Academic Resilience on Burnout in Students Working on a Thesis (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The objective of this study is to analyze the effect of social support and academic resilience on burnout in students engaged in thesis work. The study involved 324 students engaged in thesis work on the island of Java. This research method employs a quantitative approach. The data processing stage utilizes the Jamovi 2.3 software, which employs multiple linear regression models. The data were collected via an online questionnaire. The results of hypothesis testing indicate that social support has no effect on burnout. Conversely, academic resilience has a positive effect on burnout. Furthermore, social support and academic resilience simultaneously affect burnout by 2.35%, with an F value of 4.89 and a significance value of 0.008 (p